2022
DOI: 10.3390/diagnostics12061420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of High Intensity Interval Training on Axial Psoriatic Arthritis Based on MR Images

Abstract: High intensity interval training (HIIT) has been shown to benefit patients with psoriatic arthritis (PsA). However, magnetic resonance (MR) imaging has uncovered bone marrow edema (BME) in healthy volunteers after vigorous exercise. The purpose of this study was to investigate MR images of the spine of PsA patients for changes in BME after HIIT. PsA patients went through 11 weeks of HIIT (N = 19, 4 men, median age 52 years) or no change in physical exercise habits (N = 20, 8 men, median age 45 years). We acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In a later study, the same research group found no evidence of inflammation in peripheral joints and entheses in patients with PsA after completing structured HIIT for 11 weeks [48]. And even more pieces of evidence are available when reviewing the literature suggesting that HIIT is safe for patients with PsA [49].…”
Section: Discussionmentioning
confidence: 97%
“…In a later study, the same research group found no evidence of inflammation in peripheral joints and entheses in patients with PsA after completing structured HIIT for 11 weeks [48]. And even more pieces of evidence are available when reviewing the literature suggesting that HIIT is safe for patients with PsA [49].…”
Section: Discussionmentioning
confidence: 97%